Association Between Programed Cell Death-1 and CD4+ T Cell Alterations in Different Phases of Ischemic Stroke Patients - Zhang, Yi; Wei, Li; Du, Yupeng; Xie, Yirui; Wu, Wei; Yuan, Yuan (Frontiers in Cellular Neuroscience, 2018)
Objective: We aimed to analyse the alterations of subgroups in T cells during different phases post-ischaemic stroke (IS), to explore the possible mechanism of stroke-induced immune depression (SIID). Methods: Sixty-four IS patients were divided into three groups: an acute phase group, a sub-acute phase group, and a stable phase group. Fourteen healthy individuals were selected as normal controls. The phenotype distribution of T cells in the peripheral blood was analysed. Programmed cell death-1 (PD-1) and T cell immunoglobulin and mucin domain 3 (Tim-3) were detected in different phenotypes of T cells. Results: Compare with the control cells, the absolute numbers of CD4+ T cells and CD4 TCM cells showed a significant increase in acute phase; however decreased in sub-acute phase and stable phase compared with that of acute phase. The expression of PD-1 in CD4+ T cells in the stable phase showed a significant increase compared with the acute phase. The expressions of PD-1 on CD4 TCM cells and CD4 TEM cells showed significant decreases in the acute phase compared with control cells, however in the sub-acute phase and the stable phase showed a significant increase compared with that of the acute phase. Conclusions: T cell dysfunction occurred during different phases of IS, especially CD4+ T cells. PD-1 was highly expressed in CD4+ T cells of different phenotypes after the acute phase, which was associated with alterations in CD4+ T cells. Particularly, PD-1 was negatively correlated with the absolute number of TCM cells among different phenotypes of CD4+ T cells, which may be one of the possible mechanisms of stroke-induced immunodepression (SIID).